August Aaron calibrating voltmeter in Dow's Instrument Department - Dow Chemical Company (1948)
General view of Instrument calibrationist August Aaron checking the calibration of a voltmeter in the Dow Chemical Company's Instrument Department. Established in 1926, the Instrument Department was responsible for the installation and maintenance of the assorted apparatus necessary to manage the plant's production facilities and processes. The department notably maintained accurate standards for temperatures, voltage, resistance, flow and pressures against which the plant's instruments were regularly calibrated and checked for accuracy.
Keywords: Employees; Industries; Scientific apparatus and instruments; Dow Chemical Company; Voltmeters; Scientific apparatus and instruments--Calibration; Calibration; Aaron, August